A Characterization of Uniform Matroids. (1st December 2011) - Chaourar, Brahim
Abstract : This paper gives a characterization of uniform matroids by means of locked subsets. Locked subsets are 2-connected subsets, their complements are 2-connected in the dual, and the minimum rank of both is 2. Locked subsets give the nontrivial facets of the bases polytope.